Charge transport in single polymer fiber transistors in the sub-100 nm regime: temperature dependence and Coulomb blockade. (1st January 2023) - Lenz, Jakob; Statz, Martin; Watanabe, K; Taniguchi, T; Ortmann, Frank; Weitz, R Thomas
Abstract: Even though charge transport in semiconducting polymers is of relevance for a number of potential applications in (opto-)electronic devices, the fundamental mechanism of how charges are transported through organic polymers that are typically characterized by a complex nanostructure is still open. One of the challenges which we address here, is how to gain controllable experimental access to charge transport at the sub-100 nm lengthscale. To this end charge transport in single poly(diketopyrrolopyrrole-terthiophene) fiber transistors, employing two different solid gate dielectrics, a hybrid Al2 O3 /self-assembled monolayer and hexagonal boron nitride, is investigated in the sub-50 nm regime using electron-beam contact patterning. The electrical characteristics exhibit near ideal behavior at room temperature which demonstrates the general feasibility of the nanoscale contacting approach, even though the channels are only a few nanometers in width. At low temperatures, we observe nonlinear behavior in the current–voltage characteristics in the form of Coulomb diamonds which can be explained by the formation of an array of multiple quantum dots at cryogenic temperatures.